Wireless Capsule Endoscopy for Obscure Gastrointestinal Bleeding: Single Center, One Year Experience. (1st September 2004) - Tang, Shou-jiang; Christodoulo, Dimitrios; Zanati, Simon; Dubcenco, Elena; Petroniene, Rima; Cirocco, Maria; Kandel, Gabor; Haber, Gregory B; Kortan, Paul; Marcon, Norman E
Abstract : BACKGROUND: Wireless capsule endoscopy (CE) is increasingly being used in the investigation of obscure gastrointestinal (GI) bleeding, but some studies have found that many of the bleeding lesions recognized by this technique are within the reach of conventional endoscopy. METHODS: The results of CE performed in the authors' centre in a 12 month period for obscure GI bleeding were retrospectively reviewed. RESULTS: Of the 46 patients with obscure GI bleeding, CE found a definite or probable cause in 19 (41%) and a possible cause in another 10 (22%), with an overall diagnostic yield of 63%. One of these lesions was found to be within reach of conventional gastroscopy, two were within reach of push enteroscopy, four were within reach of colonoscopy and one was within reach of retrograde enteroscopy through a stoma. The percentage of patients with a bleeding source within reach of routine endoscopy but missed during pre-CE endoscopy was significantly higher for those patients having endoscopy only in the community (30% [eight of 27]) versus in the authors' centre (0% [zero of 19]). CONCLUSIONS: CE was valuable for diagnosing bleeding lesions not only within the small bowel, but also in the stomach and colon. However, 'second-look' endoscopy may be considered before ordering CE for obscure GI bleeding when local expertise is available.